Production and trade of Common carp (Cyprinus carpio) in the EU28 - Karnai, Laura; Szűcs, István (Animal welfare, Ethology and Housing Systems (AWETH), 2017)
With the rapid growth of the world's population, global meat production is nowadays unprecedented, in which fishery products play an important role as decades have been an important part of human nutrition, including fish, crustaceans and molluscs. As a result of this, freshwater fish production is getting more valuable both at European Union and domestic level. Examining at fish production of species in 2016 and according to the most up to date FAO data, with yearly 15 thousand tons of production per year in Hungary is the third largest carp producer country in the European Union (only Poland and the Czech Republic are ahead of Hungary, with 20.3 and 20.8 thousand tons per year).The object of study is to present the most important species of our country, to have an overview about the international situation of the common carp sector in the EU28, with special regard to the trade of the biggest exporting and importing countries.In our study, the secondary research was based on EUROSTAT and HCSO statistical databases. After the observation of production trends, we have examined the comparative advantages and disadvantages of trade in this sector with the help of RCA index. The basic data used to calculate the RCA index is provided by the COMTRADE International Foreign Trade Database for over 10 years. Based on the secondary research the study has a detailed examination of cause and effect relationships behind the RCA index results.
Keywords: Common carp (Cyprinus carpio) products; international trade; Revealed Comparative Advantage (RCA)